Pengaruh Media Sosial Terhadap Pendidikan Karakter Anak Di Masa Pandemi Coronavirus Disease 19 - Madyan, Madyan; Baidawi, Ahmad (Jayapangus Press, 2021)
The influence of Social Media at this time is extraordinary. In addition to communication tools, social media can also act as an information center that allows users to find out all the information that is currently happening. On the other hand, social media can also be something that is very scary for us, especially for students. Some students misuse social media not for learning purposes but for unproductive things. During the current Covid-19 pandemic, the Indonesian government has adopted a policy of online learning or online learning. Online can also be interpreted as a situation where computers or laptops can exchange information, because they are connected to the internet network, this then makes all students must have a cellphone or laptop. When students use cellphones and computers, they also access social media. The role of social media for students in achieving success or supporting learning achievement is very large. The role of teachers and parents is expected to be able to help students in limiting themselves to excessive use of social media. The purpose of this article is to determine the extent of the influence of social media on children's character education, learning achievement, the negative and positive impacts of social media and the role of teachers in schools in limiting students' use of social media.